Optimizing Transmission-Oil Vendor Selection Using AHP and FAHP Methods: A Case Study In Aircraft Services – PT. Dirgantara Indonesia (The Indonesian Journal of Business Administration, 2021)
In 2013 and 2014, Procurement function of Aircraft Services had issued a Purchase Order (PO) to a vendor to order 240 cans of transmission oil (Part Number: ROYCO555) for 17 unit of NBell-412 helicopters that should be assembled in 2014 – 2015. Due to any miss – calculation, there are 238 cans of transmission oil that were not used and has been expired in 2019. By that time, Aircraft Services had already loss a mount of money. In 2019, Procurement function had issued another PO to a vendor to order 168 can of ROYCO555 for 9 unit of Bell-412 EPI that should be assembled in 2020 – 2021. Learning from the past, the Procurement function should involve every factors (Quality, Cost, and Delivery) and had it compared by using Multi-Criteria Decision Making (MCDM) method before deciding to issued a PO to a selected Vendor. That’s why the Procurement function of Aircraft Services should had a system that could be used to automatically – select vendors based on its specific needs. Keywords: procurement, logistic, vendor selection, AHP, Fuzzy AHP